Efficient photocatalytic hydrogen peroxide generation coupled with selective benzylamine oxidation over defective ZrS3 nanobelts - Zhangliu Tian (Nature Portfolio, 2021)
Photocatalytic H2O2 generation represents a promising approach for artificial photosynthesis. Here, ZrS3 nanobelts with controllable disulfide and sulfide anion vacancies exhibit an excellent photocatalytic H2O2 generation performance together with selective oxidation of benzylamine to benzonitrile.